O trabalho de conclusão de curso pela voz dos egressos - Junges, Patrícia (2018)
The present work is about a study concerning the contributions and difficulties of the undergraduate thesis (UT) for the formation of the pedagogue. On the basis of the experiences and academic perceptions of the Pedagogy course graduates from the West Paraná University, Cascavel campus, from 2011 to 2015/2016, it is analysed the disciplines that support in the development of the senior thesis research, the relation to the researched topic and with the supervisor, and still the academic profile, formed by the institution. The study classifies itself as qualitative and discusses as methodology the bibliographical research, field work and the documents analyses, such as the Pedagogical Political Project and Teaching Plans in order to substantiate the insights obtained in the field research. For the theoretical basis it was used several authors being Saviani (2007), Libâneo (2001), Bardin (1977), Campos (2009) and Fontana (2006) some of them. According to the data collection, developed by questionnaires means, it is possible to show results in relation to the little use of the Pre-Research Project developed previously to the UT production. It also displays the lack of involvement of the graduate, as an academic, with scientific articles readings and writings, with the counselors and the scientific initiation projects contributions to the development of the senior thesis. It is evidenced the need for improvements in some cases that subsidize the development of the research in the undergraduate thesis, but, in general, the UT has been evaluated positively by the graduates for the pedagogues education.